Pelaksanaan Kurikulum Tingkat Satuan Pendidikan Pada MTs Negeri Yogyakarta II - Ali Khudrin (Balai Penelitian dan Pengembangan Agama Semarang, 2011)
The purpose of this research is to investigate the implementation of Kurikulum Tingkat Satuan Pendidikan (School-Based Curriculum) in MTsN Yogyakarta II. Using descriptive qualitative method, the research successfully reveals that the MTsN II Yogyakrta provides some steps for implementing the School-Based Curriculum: preparation, implementation, and evaluation. The first step, preparation, is started from making rules, regulations, technical guidelines and socialization, continued with organizing documents I and II of the curriculum. The second stage is the implementation of the School-Based Curriculum itself. The result of the research shows that MTsN II Yogyakarta performs the curriculum according to the document I and document II. The last step is evaluation. Some supporting factors for the implementation of the curriculum are facilities and infrastructures, instructional media, teaching materials, learning resources, and qualified human resources. While the only inhibiting factor is the fact that some teachers find difficulties in applying multi learning media.